PROBLEMS AND PROSPECTS OF ECO-TOURISM IN CHHATTISGARH - Pushpender; A. Rajshekhar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Chhattisgarh, endowed with rich natural resources, cultural diversity, waterfalls, wildlife sanctuaries, and tribal heritage, holds immense potential for tourism-led development. Despite this, the state continues to lag behind in establishing itself as a significant player on the global tourism map. The Chhattisgarh Tourism Board (CGTB), while active across various sectors for several years, has faced persistent challenges such as limited infrastructure, low public awareness, regional imbalances, and the absence of a unified tourism identity. Crucially, awareness and sensitivity toward tourism opportunities have yet to permeate different sections of society. A major barrier is the lack of an inclusive, sustainable, and well-structured strategy that aligns with the state’s ecological and cultural richness. Ecotourism, with its emphasis on environmental conservation, community involvement, and low-impact travel, offers a transformative pathway. If promoted strategically, ecotourism can stimulate local economies, preserve ecological zones, and empower indigenous communities. This paper explores the core challenges facing tourism development in Chhattisgarh and proposes a special action plan for CGTB focused on ecotourism promotion. The plan advocates for region-wise eco-circuits, community-based tourism models, improved accessibility, environmental education, and international branding. By aligning ground realities with forward-thinking policy, Chhattisgarh can emerge not only as a sustainable tourism destination but also as a model for eco-driven prosperity and inclusive development.